The diversity and abundance of Hymenoptera insects on tidal swamp rice field in Indragiri Hilir District, Indonesia - ZAHLUL IKHSAN; HIDRAYANI; YAHERWANDI; HASMIANDY HAMID (Society for Indonesian Biodiversity, 2020)
Abstract. Ikhsan Z, Hidrayani, Yaherwandi, Hamid H. 2020. The diversity and abundance of Hymenoptera insects on tidal swamp rice field in Indragiri Hilir District, Indonesia. Biodiversitas 21: 1020-1026. Hymenoptera is one of the four largest insect orders and it plays a vital role in human life as pollinators, parasitoids, and predators. Hymenoptera parasitoids are particularly important as agents of biological control of pest. The objective of this research was to study the diversity and abundance of Hymenoptera on tidal swamp rice field in Indragiri Hilir District, Riau Province, Indonesia. Samplings were conducted in 3 sub-districts of rice production centers, namely Batang Tuaka, Keritang and Reteh, using four trapping techniques (i.e. insect net, malaise trap, pitfall trap, and yellow pan trap). Shannon diversity index (H '), Krebs evenness index (E), and Jaccard similarity index (Is) were calculated. We found 4,701 individuals consisting of 39 families and 319 species of Hymenoptera at the three studied areas. Tidal swamp rice in Indragiri Hilir District had a high species diversity of Hymenoptera parasitoids and Hymenoptera predators, but a moderate species diversity of Hymenoptera pollinators. Species diversity and evenness of Hymenoptera parasitoids and predators were higher in Keritang than in Batang Tuaka and Reteh. The families of Formicidae, Braconidae, Ichneumonidae, and Scelionidae had the highest number of species, while Formicidae, Scelionidae, Diapriidae, and Braconidae had the highest number of individuals. Based on these findings, the abundance and diversity of Hymenoptera insects in Indragiri Hilir District have the potentials to be developed as biological agents to control pests on tidal swamp rice in this area.